DESIGN OF PIEZOELECTRIC POWER PLANT IN SLEEP POLICE BASED ON BLUFF BODY BASED ON KANTILEVER SYSTEM - Yusniati Yusniati (Jurnal Elektro dan Telkomunikasi, 2019)
Indonesia need for electricity predicted increase every year, this can cause Indonesia to become an energy importer in the coming year. These problems can be overcome by developing alternative energy, one of which is utilizing waste vibration energy or pressure energy from the movement of motorized vehicles, cars and pedestrians and even gusts of wind in the use of piezoelectric speed bumps. Piezoelectric is an energy harvester. Piezoelectric with cantilever mechanism produces vibrations and deflections repeatedly, causing electrical voltage. Piezoelectric speed bump designed in this study consists of a speed bump system that serves to receive input from motor vehicle pressure, a piezoelectric cantilever system as a component of producing electrical energy and a harvesting energy system as a harvester of energy from piezoelectric material. One system module consists of a piezoelectric parallel circuit connected with a buck converter MB39C811. In this paper, we will discuss the mechanism of design analysis and modeling of piezoelectric power generation systems in bluff body-based speed bumps with cantilever systems to variations in speed of motorized vehicles by means of physical modeling. In the bluff body piezoelectric bump, it is seen that the flow of air as it passes through a triangle section increases in speed so that the vortex produced has a high speed. This is what causes high vibrations in the piezoelectricity so that the maximum electric voltage and the average electric voltage have the highest value. Piezoelectric speed bumps are capable of producing electrical power with 60 times the input of a motorized vehicle over 2,166mWh with an efficiency of 2.87% compared to manual input.